L'amour conjugal sous l'angle sociologique: des pratiques à la théorie - Belleau, Hélène; Piazzesi, Chiara; Seery, Annabelle (Institut national de la recherche scientifique, 2020)
Cet article propose une réflexion sociologique sur l’amour conjugal contemporain d’un point de vue théorique et empirique. À partir de données recueillies sur les arrangements financiers de personnes vivant en couple et de la littérature sociologique sur l’amour, les auteures dégagent une sémantique de la conjugalité contemporaine illustrée par huit « règles de sens », mobilisées par les acteurs pour répondre aux défis des relations intimes. L’analyse permet d’observer les décalages entre différentes logiques amoureuses d’une part, et de l’autre entre les logiques de l’amour et les réalités sociales. Les propos des conjoints révèlent l’intégration d’éléments qui tiennent de logiques divergentes dans un même univers de sens : des règles de sens favorisant l’idéalisation mythique conjuguées à celles organisées autour des images du travail sur la relation, de la communication thérapeutique et de la prise en charge entrepreneuriale de la relation. Cette analyse empirique conduit les auteures à cerner une double confusion dans la littérature contemporaine sur l’amour et les couples.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; corps; couple; cours; discipline; famille; hétérosexualité; inégalités; premier cycle; privilèges; périodes historiques; québec; relations amoureuses; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Data feminism - D'Ignazio, Catherine; Klein, Lauren F. (ideas series, 2020)
"A new way of thinking about data science and data ethics that is informed by the ideas of intersectional feminism. Today, data science is a form of power. It has been used to expose injustice, improve health outcomes, and topple governments. But it has also been used to discriminate, police, and surveil. This potential for good, on the one hand, and harm, on the other, makes it essential to ask: Data science by whom? Data science for whom? Data science with whose interests in mind? The narratives around big data and data science are overwhelmingly white, male, and techno-heroic. In Data Feminism, Catherine D'Ignazio and Lauren Klein present a new way of thinking about data science and data ethics--one that is informed by intersectional feminist thought. Illustrating data feminism in action, D'Ignazio and Klein show how challenges to the male/female binary can help challenge other hierarchical (and empirically wrong) classification systems. They explain how, for example, an understanding of emotion can expand our ideas about effective data visualization, and how the concept of invisible labor can expose the significant human efforts required by our automated systems. And they show why the data never, ever 'speak for themselves.' Data Feminism offers strategies for data scientists seeking to learn how feminism can help them work toward justice, and for feminists who want to focus their efforts on the growing field of data science. But Data Feminism is about much more than gender. It is about power, about who has it and who doesn't, and about how those differentials of power can be challenged and changed."-
Keywords: approches et analyses; discipline; données scientifiques; histoire et politique; intersectionnalité; patriarcat; privilèges; projet charge mentale; pédagogie; racisme; rapports de pouvoir; ressource en ligne; sciences; sciences humaines; systèmes d'oppressions; thématiques; travail; travail scientifique; épistémologie

Collectiviser la question parentale: les apports des parenting cultures studies - Martin, Claude (Lien social et Politiques, 2020)
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; care; cours; discipline; europe; france; justice sociale; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques